Exercise training prevents diastolic dysfunction induced by metabolic syndrome in rats (Clinics, 2012)
OBJECTIVE: High fructose consumption contributes to the incidence of metabolic syndrome and, consequently, to cardiovascular outcomes. We investigated whether exercise training prevents high fructose diet-induced metabolic and cardiac morphofunctional alterations. METHODS: Wistar rats receiving fructose overload (F) in drinking water (100 g/l) were concomitantly trained on a treadmill (FT) for 10 weeks or kept sedentary. These rats were compared with a control group (C). Obesity was evaluated by the Lee index, and glycemia and insulin tolerance tests constituted the metabolic evaluation. Blood pressure was measured directly (Windaq, 2 kHz), and echocardiography was performed to determine left ventricular morphology and function. Statistical significance was determined by one-way ANOVA, with significance set at p